2001
DOI: 10.1086/322955
|View full text |Cite
|
Sign up to set email alerts
|

A Measurement of the Three‐dimensional Clustering of CivAbsorption‐Line Systems on Scales of 5–1000h−1Mpc

Abstract: We examine the three-dimensional clustering of C IV absorption-line systems using an extensive catalog of QSO heavy-element absorbers drawn from the literature. We measure clustering by a volumeweighted integral of the correlation function called the reduced second-moment measure, and include information from both along and across QSO lines of sight, thus enabling a full determination of the three-dimensional clustering of absorbers, as well as a comparison of alongÈ and acrossÈline-of-sight clustering propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Söchting, Clowes & Campusano 2004, and references therein) whilst QSOs themselves seem to cluster over similar distances (Croom et al 2004; Porciani, Magliocchetti & Norberg 2004). Even larger scale structures have been reported ranging from tens (Steidel et al 1998; Söchting, Clowes & Campusano 2002; Haines et al 2003) to hundreds (Quashnock, Vanden Berk & York 1996; Loh, Quashnock & Stein 2001; Haines, Campusano & Clowes 2004) of comoving Mpc. Large‐scale structures of many Mpc are therefore pervasive from the lowest (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Söchting, Clowes & Campusano 2004, and references therein) whilst QSOs themselves seem to cluster over similar distances (Croom et al 2004; Porciani, Magliocchetti & Norberg 2004). Even larger scale structures have been reported ranging from tens (Steidel et al 1998; Söchting, Clowes & Campusano 2002; Haines et al 2003) to hundreds (Quashnock, Vanden Berk & York 1996; Loh, Quashnock & Stein 2001; Haines, Campusano & Clowes 2004) of comoving Mpc. Large‐scale structures of many Mpc are therefore pervasive from the lowest (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tytler, Sandoval & Fan (1993) saw no sign of periodicity on 10–210 Mpc scales in the 3D distribution of 268 Mg ii absorption systems. Loh, Quashnock & Stein (2001) examined the 3D distribution of 345 C iv systems from 276 QSOs and found evidence for clustering on scales up to 220 Mpc ( q 0 = 0.5). Vanden Berk et al (2000) found four metal‐line absorption systems towards QSOs near to the HDF, two of which have redshifts that place them in the second most populated peak in the galaxy redshift distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Line parameters are consistent with a photoionized gas (Rauch et al 1996). The C iv absorbers appear to be highly clustered (Sargent, Boksenberg & Steidel 1988; Petitjean & Bergeron 1994; Loh, Quashnock & Stein 2001) and have been thought to originate in gas clouds orbiting in galactic haloes (Sargent et al 1979; Steidel 1993; Petitjean & Bergeron 1994; Mo & Miralda‐Escudé 1996). Hydrodynamical simulations also support a picture in which high‐redshift C iv arises in protogalactic clumps (PGCs), i.e.…”
Section: Introductionmentioning
confidence: 99%